2015
DOI: 10.4236/ajps.2015.614239
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Phylogenetic Relationships of Caryopteris incana in the Tsushima Islands, Japan, Using DNA Sequence Analysis

Abstract: Caryopteris incana is a perennial shrub distributed in the temperate zone of the East Asia. It is found in West Kyushu in Japan, where it is designated as an endangered species. Tsushima, Nagasaki, which experienced repeated connection and fragmentation between the Korean Peninsula and Japan, is an island on the route along which C. incana moved to Japan from continental Asia. We conducted field work and confirmed the genetic structure of populations using DNA sequence analysis to construct a detailed distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
(22 reference statements)
0
6
1
Order By: Relevance
“…Like the sequence variation of the populations on the Tsushima Islands [18], several substitution sites between Genbank registration sequences and those of the study populations were confirmed in the matK, trnL-trnF and rpl32-trnL regions( Table 2). However, there were no indications of substitution among the study populations in these sites.…”
Section: Sequence Variationsmentioning
confidence: 53%
See 4 more Smart Citations
“…Like the sequence variation of the populations on the Tsushima Islands [18], several substitution sites between Genbank registration sequences and those of the study populations were confirmed in the matK, trnL-trnF and rpl32-trnL regions( Table 2). However, there were no indications of substitution among the study populations in these sites.…”
Section: Sequence Variationsmentioning
confidence: 53%
“…We have confirmed 72 natural populations by conducting fieldwork in the Tsushima Islands, Nagasaki [18]. In this study, we investigated the Nagasaki Mainland, Goto Islands, some remote islands, and the western parts of Saga adjacent to the Nagasaki and Koshikijima Islands, based on the report by Itow and Kawasato [16] (Figure 1).…”
Section: Field Workmentioning
confidence: 71%
See 3 more Smart Citations